2003
DOI: 10.1038/sj.bjp.0705325
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐1 inhibits TNFα‐induced iNOS expression in 3T3‐F442A adipocytes

Abstract: 1 Endothelin-1 (ET-1) and tumor necrosis factor a (TNFa) by their action on adipocytes have been independently linked to the pathogenesis of insulino-resistance. In isolated adipocytes, TNFa induces the expression of the inducible nitric oxide synthase (iNOS). The purpose of the present work was, in the 3T3-F442A adipocyte cell line, to characterise TNFa-induced iNOS expression and to determine whether or not ET-1 could influence TNFa-induced iNOS expression and NO production. 2 In differentiated 3T3-F442A, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…We have used the PI3K inhibitor LY294002 to demonstrate that HB-EGF-mediated activation of PI3K is necessary for HB-EGF-induced suppression of NF-B activation and NO production induced by a combination of proinflammatory cytokines. The present demonstration that PI3K inhibition prevents the effects of HB-EGF on NF-B activation and NO production is reminiscent of the report demonstrating that endothelin-1-induced inhibition of iNOS expression in adipocytes is dependent on PI3K activation (40). Additionally, inhibition of PI3K induced the expression of iNOS in LPS stimulated microglial cells (8,9).…”
Section: Discussionsupporting
confidence: 62%
“…We have used the PI3K inhibitor LY294002 to demonstrate that HB-EGF-mediated activation of PI3K is necessary for HB-EGF-induced suppression of NF-B activation and NO production induced by a combination of proinflammatory cytokines. The present demonstration that PI3K inhibition prevents the effects of HB-EGF on NF-B activation and NO production is reminiscent of the report demonstrating that endothelin-1-induced inhibition of iNOS expression in adipocytes is dependent on PI3K activation (40). Additionally, inhibition of PI3K induced the expression of iNOS in LPS stimulated microglial cells (8,9).…”
Section: Discussionsupporting
confidence: 62%
“…It has been shown that ET-1 inhibits the induction of iNOS mRNA and protein by tumor necrosis factor alpha in adipocytes. 31 In a former study, the expression of iNOS in subcutaneous tissue was found to be 10-fold lower than eNOS, while iNOS protein was not detected in lean persons and only at low concentrations in obese patients, 23 nNOS being undetectable. Our iNOS levels were comparable to those of eNOS, which might be due to the operative setting (general anesthesia, laparotomy).…”
Section: Discussionmentioning
confidence: 92%
“…However, this concentration may increase significantly in inflammatory conditions or after exercise (51). For example, a greater than five-fold increase in adipocyte nitrite concentration has been reported after cytokine stimulation of iNOS (52). In these chronic inflammatory conditions, tissue nitrite concentration may approach the levels used in this study (50–100μM).…”
Section: Discussionmentioning
confidence: 99%